Effect of constipation on readmission for heart failure in patients with acute heart failure - Shigeto Namiuchi; Atsushi Tanita; Shinichiro Sunamura; Kenta Onodera; Tsuyoshi Ogata; Kazuki Noda; Toru Takii; Yoshio Nitta; Seijiro Yoshida (ESC Heart Failure, 2024)
Abstract Aims Constipation is a common gastrointestinal disorder that is associated with a high cardiovascular event rate in the general population. Although constipation is common in patients with cardiovascular diseases, only a few studies have examined the relationship between constipation and the prognosis of patients with heart failure. This study aimed to evaluate the effects of constipation on the prognosis of patients with acute heart failure. Methods and results We investigated 397 patients admitted to our hospital from December 2020 to December 2022 with acute heart failure (mean age, 81 ± 13 years; 54% men). Patients with constipation were defined as those either taking laxatives regularly or diagnosed with constipation according to the International Statistical Classification of Diseases and Related Health Problems. During the follow‐up periods (median, 173 days), 35 patients died, and 74 experienced readmission due to heart failure. Kaplan–Meier analysis before and after propensity score matching using 14 variables revealed that the risk of readmission due to heart failure was significantly higher in patients with constipation than in those without (before: log‐rank P = 0.014, after: log‐rank P = 0.0027). The adjusted Cox proportional hazards analysis revealed that the hazard ratio for readmission due to heart failure was 2.61 (95% confidence interval, 1.38–4.94, P = 0.0032). The risk of all‐cause death was not significantly different between the two groups (hazard ratio, 1.76; 95% confidence interval, 0.61–5.06; P = 0.30). Conclusions Constipation status was strongly associated with a higher risk of readmission for heart failure in patients with acute heart failure.